Long-term depression is a stroke risk factor - Kocer, Emel; Kocer, Abdulkadir; Degirmenci, Yildiz; Eryilmaz, Mehmet (My University, 2011)
Background and Aim: Only a few studies have evaluated depression prevalence in pre-stroke period in comparison to controls. We investigated this association based on a hospitalised stroke population.